Diffusion properties of self-propelled particles in cellular flows. Issue 23 (29th May 2020) - Caprini, Lorenzo; Cecconi, Fabio; Puglisi, Andrea; Sarracino, Alessandro
Abstract : We study the dynamics of a self-propelled particle advected by a steady laminar flow unveiling its diffusive properties due to the interplay between the active force and the convective flow. Abstract : We study the dynamics of a self-propelled particle advected by a steady laminar flow. The persistent motion of the self-propelled particle is described by an active Ornstein–Uhlenbeck process. We focus on the diffusivity properties of the particle as a function of persistence time and free-diffusion coefficient, revealing non-monotonic behaviors, with the occurrence of a minimum and a steep growth in the regime of large persistence time. In the latter limit, we obtain an analytical prediction for the scaling of the diffusion coefficient with the parameters of the active force. Our study sheds light on the effect of a flow-field on the diffusion of active particles, such as living microorganisms and motile phytoplankton in fluids.